Experimental identification and control of a cantilever beam using ERA/OKID with a LQR controller - Gagg F., L. A. [UNESP] (2014)
This paper presents an experimental study of the system identification and vibration control of a cantilever beam. For system identification, a white noise was applied, and the response signal was measured. These signals were used to feed the eigensystem realization algorithm-Observer/Kalman Filter identification method. The identified system was reduced using the Hankel norm model. An linear quadratic regulator controller was projected to operate just on the first two natural frequencies of the structure. The damping ratio of the first mode was effectively increased from 0.009 to 0.046. © 2014 Brazilian Society for Automatics - SBA.